2007
DOI: 10.1016/j.jcis.2007.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between hairy rod anionic conjugated polyelectrolytes and nonionic alkyloxyethylene surfactants in aqueous solution: Observations from cloud point behaviour

Abstract: The effect of three anionic, hairy-rod fluorene based conjugated polyelectrolytes on the cloud points of the alkyloxyethylene surfactants C10E3, C12E4, C12E5, and C12E6 has been studied in aqueous solution. Although the association behaviour of these rigid polymers with surfactants is different from that of more flexible polyelectrolytes, both types of polymers are seen to increase the cloud points, probably as a consequence of associative interactions. The possible importance of Coulombic interactions is sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…In the case of surfactants, this occurs in the region of the critical micelle concentration (cmc) [24,30,32]. Various factors appear to be involved in the formation and break-up of CPE aggregates [28,29,30,31,33,34], although, as of yet, there is no consensus as to the dominant interaction(s). Edman and co-workers have demonstrated, using pulse-field-gradient Nuclear magnetic resonance (NMR,) photoluminescence and Raman spectroscopy, that the CPE poly{9,9′-bis[6″-( N , N , N -trimethylammonium)-hexylfluorene- alt -1,4-phenylene] dibromide} forms aggregates in methanol [28]; they have also suggested that π,π interactions of backbones, coupled with electrostatic screening of ionic side chains by solvent, are important effects.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of surfactants, this occurs in the region of the critical micelle concentration (cmc) [24,30,32]. Various factors appear to be involved in the formation and break-up of CPE aggregates [28,29,30,31,33,34], although, as of yet, there is no consensus as to the dominant interaction(s). Edman and co-workers have demonstrated, using pulse-field-gradient Nuclear magnetic resonance (NMR,) photoluminescence and Raman spectroscopy, that the CPE poly{9,9′-bis[6″-( N , N , N -trimethylammonium)-hexylfluorene- alt -1,4-phenylene] dibromide} forms aggregates in methanol [28]; they have also suggested that π,π interactions of backbones, coupled with electrostatic screening of ionic side chains by solvent, are important effects.…”
Section: Introductionmentioning
confidence: 99%
“…28 Indications that anionic CPEs may be incorporated within mesophases formed in the binary nonionic alkyloxyethylene surfactant-water systems come from their effects on the surfactant cloud points. 29 We have, therefore, looked at the possibility of nanostructuring these anionic CPEs to spontaneously form anisotropic lamellar phases using the C 12 E 4 -water system.…”
Section: Introductionmentioning
confidence: 99%
“…monomer unit [35]. Associative interaction between these conjugated polyelectrolytes and non-ionic surfactants is also reflected by changes in the cloud points [42]. As indicated above, ionic conjugated polyelectrolytes, such as these polyfluorenes, have a tendency to self-aggregate in poor solvents, like water.…”
Section: Enhancement Of the Emission Quantum Yieldmentioning
confidence: 92%